Charge transfer in the nanoscale and SERS: understanding the huge efficiency of the electrode potencial in tuning the CT states - Centeno-Benigno, Silvia Patricia; Ruano, Cristina; Roman-Perez, Jessica; López-Tocón, Isabel; Soto-Martín, Juan; Otero-Fernández-de-Molina, Juan Carlos (My University, 2014)
This work deals with the unexplained efficiency of the electrode potential in tuning the energy of the CT states of hybrid systems formed by molecules and metallic nano structures. Huge energy gain up to 5eV/V observed in electrochemical SERS experiences are in conflict with classical picture of metal-absorbates CT mechanism where G=1. Supported on electronic calculations of metal-molecules systems we are able to demonstrate that this "anomalous gain" is due to two different contributions.The first one is related to the sensitivity of the CT electronic states of each particular metal-molecule complex on the effective charge excess of the metal. The second contribution is originated by the enhanced electric capacitance of metallic nanoclusters and is discussed in another communication.
Conferencia oral en ICORS2014 en la sesión de "SERS and Fundamentals"
Keywords: Espectroscopía de Raman; SERS; Electrode; CT states